2022
DOI: 10.5713/ab.21.0371
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin represses lipid accumulation through inhibiting ERK1/2-PPAR-γ signaling pathway and triggering apoptosis in porcine subcutaneous preadipocytes

Abstract: Objective: Excessive lipid accumulation in adipocytes results in prevalence of obesity and metabolic syndrome. Curcumin (CUR), a naturally phenolic active ingredient, has been shown to have lipid-lowering effects. However, its underlying mechanisms have remained largely unknown. Therefore, the study aims to determine the effect of CUR on cellular lipid accumulation in porcine subcutaneous preadipocytes (PSPA) and to clarify novel mechanisms.Methods: The PSPA were cultured and treated with or without CUR. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Hassan et al 36 who conducted a recent mechanistic study concluded curcumin does have the ability to exert potent antitoxic, anti-oxidant, tissue-protective, and anti-obesity effects, hence they recommended curcumin be added to various dietary regimens to prevent or delay organ dysfunction among obese people. Tsuda et al 37 similarly agree that curcumin has anti-obesity/anti-adipogenic and anti-diabetes biological properties among others, as also observed by Labban et al 38 and can be seen to have a high probability of preventing or reducing the magnitude of various obesity states through well defined biochemical signaling pathways and others that may be active even on preadipocytes, 39 as well as in reversing or modulating age and obesity associated metabolic diseases. 16,40 Most noteworthy is that it has also been shown that curcumin is a bioactive compound that may not only have multiple beneficial health and anti-oxidative effects, 41 but a beneficial effect on the course of SARS-CoV-2 infection and that might hence be helpful in the prevention of long-COVID complications-and others that are closely associated with cardiovascular diseases and obese states.…”
Section: Resultsmentioning
confidence: 61%
“…Hassan et al 36 who conducted a recent mechanistic study concluded curcumin does have the ability to exert potent antitoxic, anti-oxidant, tissue-protective, and anti-obesity effects, hence they recommended curcumin be added to various dietary regimens to prevent or delay organ dysfunction among obese people. Tsuda et al 37 similarly agree that curcumin has anti-obesity/anti-adipogenic and anti-diabetes biological properties among others, as also observed by Labban et al 38 and can be seen to have a high probability of preventing or reducing the magnitude of various obesity states through well defined biochemical signaling pathways and others that may be active even on preadipocytes, 39 as well as in reversing or modulating age and obesity associated metabolic diseases. 16,40 Most noteworthy is that it has also been shown that curcumin is a bioactive compound that may not only have multiple beneficial health and anti-oxidative effects, 41 but a beneficial effect on the course of SARS-CoV-2 infection and that might hence be helpful in the prevention of long-COVID complications-and others that are closely associated with cardiovascular diseases and obese states.…”
Section: Resultsmentioning
confidence: 61%
“…Various studies have pointed out the inhibitory effects of curcumin on NF- κ B signalling pathways as the main regulatory switcher of inflammatory pathways in cells (79,80) . Another possible effect of curcumin on adipokines can be related to transcription factors such as peroxisome proliferator-activated receptor- γ (PPAR γ ) (81) , sterol regulatory element-binding transcription factor 1 (82) , and CCAAT/enhancer-binding protein (C/EBP) (83) which affect the secretion of adipokines (84) . These transcription factors have various functions in the body including regulation of lipid metabolism, insulin sensitivity, inflammation and adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Novel DEMiR-target genes have also been reported to be important for lipid metabolism and fat deposition ( Supplementary File S9 ), including novel-m0048-3p ( LEP , LEPR , LPL , CYB5R1 , VLDLR , CPT1A , PPARD ), novel-m0050-3p ( ACACA , PLIN1 , THRSP ), and novel-m0104-5p ( FFAR4 , PPARA , APOE ) [ 60 , 61 , 62 ]. Furthermore, KEGG and GO analyses revealed that the target genes of 36 DEMiRs were significantly enriched for terms and pathways related to fat cell differentiation, fatty acid biosynthesis, and lipid metabolism, such as the PPAR signaling pathway [ 63 ], PI3K–Akt signaling pathway [ 64 ], mTOR signaling pathway [ 65 ], and Wnt signaling pathway [ 66 ].…”
Section: Discussionmentioning
confidence: 99%